Intertextual analysis of the story "Cherry Brandy": Shalamov – Mandelstam – Tyutchev – Verlaine (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
In the article study the transformation of the legend of the death of Osip Mandelstam in the story Varlam Shalamov "Cherry Brandy" in the ontological aspect. Also identified and described some features "plutonic" concept of fiction, which presents the work of Shalamov.
Keywords: V. T. Shalamov; O. E. Mandelstam; myth; intertextuality; ontological poetics